Cones and craters on Mount Pavagadh, Deccan Traps: Rootless cones? - SHETH, HC; MATHEW, G; PANDE, K; MALLICK, S; JENA, B (INDIAN ACADEMY SCIENCES, 2004)
Rootless cones, also (erroneously) called pseudocraters, form due to explosions that ensue when a lava flow enters a surface water body, ice, or wet ground. They do not represent primary vents connected by vertical conduits to a subsurface magma source. Rootless cones in Iceland are well studied. Cones on Mars, morphologically very similar to Icelandic rootless cones, have also been suggested to be rootless cones formed by explosive interaction between surface lava flows and ground ice. We report here a group of gentle cones containing nearly circular craters from Mount Pavagadh, Deccan volcanic province, and suggest that they are rootless cones. They are very similar morphologically to the rootless cones of the type locality of Myvatn in northeastern Iceland. A group of three phreatomagmatic craters was reported in 1998 from near Jabalpur in the northeastern Deccan, and these were suggested to be eroded cinder cones. A recent geophysical study of the Jabalpur craters does not support the possibility that they are located over volcanic vents. They could also be rootless cones. Many more probably exist in the Deccan, and volcanological studies of the Deccan are clearly of value in understanding planetary basaltic volcanism.